Paranoid thinking, cognitive bias and dangerous neighbourhoods: implications for perception of threat and expectation of victimisation - Jack, Alexander; Egan, Vincent (SAGE Publications, 2016)
Background: Paranoid thinking is prevalent in the non-clinical population and cognitive mechanisms of heuristic reasoning and jumping to conclusions bias contributes to its formation and maintenance.